Vehicle detection based on improved multitask cascaded convolutional neural network and mixed image enhancement. Issue 17 (8th March 2021) - Xu, Ke; Gong, Hua; Liu, Fang
Abstract : In order to increase the detection effect of fuzzy vehicles and small size vehicles, an improved multitask cascaded convolutional neural network (IMC‐CNN) based on mixed image enhancement is proposed. Firstly, contrast limited adaptive histogram equalisation and multi‐scale Retinex are used to enhance images. Mixed image enhancement can effectively solve the problems of image blurring, low contrast and uneven illumination when the imaging environment is not ideal. IMC‐CNN includes two stages: object location and object classification. The object location network based on multi‐layer feature fusion can locate and extract the object from complex background, and output regions contain only a single vehicle object. The object classification network is a lightweight convolutional neural network with only two convolutional layers, which can effectively reduce information loss and improve the classification accuracy of small objects and fuzzy objects. In addition, online hard example mining algorithm and focal loss function are adopted in network training. These strategies can solve the problem of unbalance between positive and negative samples. To verify the validity of the proposed algorithm, the experiments are performed on SYIT‐Fuzzy dataset and COCO‐Vehicle dataset. Compared with Faster R‐CNN, YOLO v4 and other recent models, the average classification accuracy of the proposed method is significantly increased.